Contrast-enhanced harmonic endoscopic ultrasound - Săftoiu, A.; Dietrich, C. F.; Vilmann, P. (Endoscopy, 2012)
Second-generation intravenous blood-pool ultrasound contrast agents are increasingly used in endoscopic ultrasound (EUS) for characterization of microvascularization, differential diagnosis of benign and malignant focal lesions, and improving staging and guidance of therapeutic procedures. Although initially used as Doppler signal enhancers, second-generation microbubble contrast agents are now used with specific contrast harmonic imaging techniques, which benefit from the highly nonlinear behavior of the microbubbles. Contrast-specific modes based on multi-pulse technology are used to perform contrast-enhanced harmonic EUS based on a very low mechanical index (0.08 – 0.12). Quantification techniques based on dynamic contrast-enhanced ultrasound have been recommended for perfusion imaging and monitoring of anti-angiogenic treatment, mainly based on time–intensity curve analysis. Most of the clinical applications include the differential diagnosis of focal pancreatic masses, with adenocarcinoma having a distinct hypovascular (hypo-enhanced) appearance compared with neuroendocrine tumors, which are hypervascular (with strong arterial hyper-enhancement). However, pseudotumoral chronic pancreatitis and autoimmune pancreatitis also have an iso- or hypervascular appearance, making the differential diagnosis difficult. Even more promising is the use of dynamic contrast-enhanced harmonic EUS for the longitudinal monitoring of the effects of chemotherapy and/or anti-angiogenic therapy in advanced digestive cancers, which are difficult to examine by conventional cross-sectional imaging techniques.